2013
DOI: 10.1002/bdrb.21054
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity Assessment of Artemether in Juvenile Rats

Abstract: As in the adult rat, oral administration of artemether in the juvenile rat is not associated with the neurotoxicity produced by intramuscular administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…ATM doses used in the present work were based on a previous study (Beckman et al 2013), that reported neurotoxicity in juvenile rats by different protocols using doses from 20 to 200 mg kg −1 day −1 for 7 days, by the oral route. They showed that doses higher than 30 mg kg −1 day −1 increased mortality, renal necrosis and brain haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…ATM doses used in the present work were based on a previous study (Beckman et al 2013), that reported neurotoxicity in juvenile rats by different protocols using doses from 20 to 200 mg kg −1 day −1 for 7 days, by the oral route. They showed that doses higher than 30 mg kg −1 day −1 increased mortality, renal necrosis and brain haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Although artemisinins have been known to cause neurotoxic effects in animals [ 18 - 20 ], there is no conclusive evidence of neurotoxic effects in adults or children [ 4 , 21 ]. Further, neurotoxicity has not been observed after oral artemether administration [ 22 ], suggesting that it is the total exposure over an extended period that leads to this toxicity, which can occur with intramuscular administration because of its slow continuous absorption without first pass effect. However, it was not possible to calculate reliable AUC in infants in this study because of the limitations in both the number and total volume of blood samples obtained from this population.…”
Section: Discussionmentioning
confidence: 99%
“…Higher exposures (C max and AUC) and greater systemic toxicity with decreasing age of rat pups after artemether oral administration were reported [ 22 ]. Greater systemic toxicity was observed in the younger animals (mortality in seven to 13-day-old pups started at 30 mg/kg/day dose but no mortality in older pups was observed at this dose).…”
Section: Discussionmentioning
confidence: 99%
“…It is not recommended to use ACTs during the first trimester due to side effects observed in preclinical models [24]. Currently, sulfadoxine-pyrimethamine is used in pregnant women as an intermittent preventive treatment to reduce infections and improve pregnancy outcomes.…”
Section: Pharmacological Approachesmentioning
confidence: 99%